Preparation of nanocrystalline nickel oxide from nickel hydroxide using spark plasma sintering and inverse Hall-Petch related densification. Issue 13 (September 2018) - Ponnuchamy, Mohan B.; Muralikrishna, G. Mohan; Mannava, Venkateswara Rao; Srinivas Reddy, G.
Abstract: Nanocrystalline nickel oxide (NiO) was prepared from nickel hydroxide by Spark plasma sintering (SPS) and the mechanisms involved in the densification of NiO were studied. Reverse precipitated nickel hydroxide powders were SPS processed at 400, 600 and 700 °C with 70 MPa pressure. Pure NiO with 12 nm crystallite size formed after 400 °C sintering process. However NiO grains had grown to 18 and 38 nm after 600 and 700 °C sintering respectively. NiO pellets prepared using 600 and 700 °C SPS sintering schedules had relative densities of 83% and 94% respectively. Two displacement rate regimes were observed during densification of NiO in both 600 and 700 °C sintering processes. Decomposition of nickel hydroxide and particle sliding of NiO led to first displacement rate maximum while inverse Hall-Petch based plastic deformation facilitated densification during the constant second displacement rate regime. No densification occurred during sintering holding times indicating the limited role that diffusion played during densification.